Student teachers’ perceptions of technical subjects - Wendy J. Dow (2002)
This paper explores the extent to which a cohort of student teachers studying for a one-year Post Graduate Certificate of Education in a Scottish university hold stereotypical views about subjects in the curriculum of Scottish secondary schools and of the pupils who select these subjects for study. In particular, a comparison between physics and technological studies is made. Technological studies, which is a relatively new area in the Scottish curriculum, was introduced in an attempt to provide a course with a high degree of academic content and was perceived to be of particular relevance to pupils intent on pursuing a career in engineering. Despite these intentions, uptake of the course in schools in the west of Scotland has shown a steady decline. It is suggested that the persistence of traditional stereotypes regarding the non-academic, skills-based nature of subjects in the technical curriculum may be a factor contributing to the demise of technological studies. The results from this small sample suggest that stereotypical views do exist, at least for the particular group of student teachers surveyed. These findings are discussed within the context of factors which have been found to influence pupil choice of subjects in secondary schools.